The Theory Applications of Finance and Macroeconomics - Hamdi, Helmi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Recently, the world economy has witnessed some turbulence and instability, both of which have raised concerns and added threats to the global economy. For example, climate change, trade war, regional political tension, Brexit, and the very recent Coronavirus epidemic have hit several countries across all continents at an astonishing rate and are among some of the factors that have increased uncertainty. We have also noticed a surge in technological innovations and their implications in the banking and financial sectors. Today, we talk about blockchain, fintech, insurtech, regtech, and big tech, which have changed the business model of banks, financial institutions, and also the management model for firms and public administration. To get better insight into all these trends, economists have used the finance and macroeconomic theory to analyze the micro- and macroeconomic consequences of all these events and to study their impacts on economic and financial sector stability, as well as economic development and growth. In this Special Issue, Economies is inviting researchers and academicians to submit their work to a Special Issue dedicated to "The Theory Applications of Finance and Macroeconomics". Some of the topics that contribute to the Issue might address issues of trade tension, climate change, blockchain and cryptocurrencies, financial liberalization, macroeconomic issues, principles of international finance, and open economy macroeconomics.